A Planar‐Structured Dinuclear Cobalt(II) Complex with Indirect Synergy for Photocatalytic CO2‐to‐CO Conversion - Gong, Yun‐Nan; Zhao, Si‐Qi; Wang, Hong‐Juan; Ge, Zhao‐Ming; Liao, Chen; Tao, Ke‐Ying; Zhong, Di‐Chang; Sakai, Ken; Lu, Tong‐Bu (Angewandte Chemie International Edition, 2024)
Dinuclear metal synergistic catalysis (DMSC) has been proved an effective approach to enhance catalytic efficiency in photocatalytic CO2 reduction reaction, while it remains challenge to design dinuclear metal complexes that can show DMSC effect. The main reason is that the influence of the microenvironment around dinuclear metal centres on catalytic activity has not been well recognized and revealed. Herein, we report a dinuclear cobalt complex featuring a planar structure, which displays outstanding catalytic efficiency for photochemical CO2‐to‐CO conversion. The turnover number (TON) and turnover frequency (TOF) values reach as high as 14457 and 0.40 s−1 respectively, 8.6 times higher than those of the corresponding mononuclear cobalt complex. Control experiments and theoretical calculations revealed that the enhanced catalytic efficiency of the dinuclear cobalt complex is due to the indirect DMSC effect between two CoII ions, energetically feasible one step two‐electron transfer process by Co2I,I intermediate to afford Co2II,II(CO22−) intermediate and fast mass transfer closely related with the planar structure. A planar‐structured dinuclear cobalt(II) complex exhibits an indirect synergistic catalysis effect between two Co(II) sites for photocatalytic CO2‐to‐CO conversion, with TON and TOF values of 14457 and 0.40 s−1 respectively, which is 8.6‐fold improvement than that of the corresponding mononuclear counterpart.